2023
DOI: 10.1101/2023.04.24.23289033
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resistance and prevalence implications of doxycycline post-exposure prophylaxis for gonorrhea prevention in men who have sex with men: a modeling study

Abstract: Background Doxycycline post-exposure prophylaxis (DoxyPEP) has demonstrated efficacy for prevention of bacterial sexually transmitted infections. To inform policy decisions on the use of DoxyPEP for gonorrhea prevention, we used a mathematical model to investigate its impact on resistance dynamics and the burden of infection in men who have sex with men (MSM). Methods and Findings Using a deterministic compartmental model of gonorrhea transmission in an MSM population, we introduced DoxyPEP at various uptake l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Increasing DoxyPEP uptake and higher initial doxycycline resistance prevalence accelerated the loss of efficacy and had minimal impact on extending the clinical lifespan of ceftriaxone for N. gonorrhoeae treatment. The model suggested that while DoxyPEP is effective in the short-term its reduction in cumulative infections was only around 13.5-14.6% at 20 years, and it hastens doxycycline resistance to 87% within 1.8-14.1 years, depending on uptake (10-75%) 43 .…”
Section: Antimicrobial Resistance and Microbiome Disruptionmentioning
confidence: 99%
“…Increasing DoxyPEP uptake and higher initial doxycycline resistance prevalence accelerated the loss of efficacy and had minimal impact on extending the clinical lifespan of ceftriaxone for N. gonorrhoeae treatment. The model suggested that while DoxyPEP is effective in the short-term its reduction in cumulative infections was only around 13.5-14.6% at 20 years, and it hastens doxycycline resistance to 87% within 1.8-14.1 years, depending on uptake (10-75%) 43 .…”
Section: Antimicrobial Resistance and Microbiome Disruptionmentioning
confidence: 99%
“…Future trials assessing oropharyngeal gonorrhoea treatments should collect comprehensive pharmacokinetic data so that their doses can be optimised using robust modelling methods [129] and the use of in-vitro models may help to identify drugs that are distributed into oral tissue before being tested in clinical trials to improve successful outcomes [130] given only 13% of infectious diseases drugs entering clinical trials get FDA approval, most discarded in phase 2 [131]. Lastly, it remains uncertain what the effects will be of emerging interventions such as doxycycline postexposure prophylaxis on the development of oropharyngeal gonorrhoea incidence and drug resistance and the role of meningococcal vaccines as preventive measures [132,133,134 ▪ ,135 ▪▪ ,136,137,138 ▪▪ ,139–141].…”
Section: Treatment For Oropharyngeal Infectionsmentioning
confidence: 99%
“…Several modeling studies have described the transmission of CT and NG among MSM [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ], which cluster in a few Western countries, mainly from the US [ 9 , 13 , 14 , 19 , 25 , 26 , 27 , 28 , 35 , 36 ] and Australia [ 18 , 22 , 23 , 24 , 32 , 40 , 41 , 42 , 43 ]. In Europe, notable modeling studies have been conducted in the UK [ 31 , …”
Section: Introductionmentioning
confidence: 99%
“…Several modeling studies have described the transmission of CT and NG among MSM , which cluster in a few Western countries, mainly from the US [9,13,14,19,[25][26][27][28]35,36] and Australia [18,[22][23][24]32,[40][41][42][43]. In Europe, notable modeling studies have been conducted in the UK [31,37,38,45] and The Netherlands [17,29,30,33,39,44], with few papers from France [34], Belgium [8,16] and Switzerland [20,21].…”
Section: Introductionmentioning
confidence: 99%